Mathematics
parrcaitlin
19

How would I solve these?  (-3xy)³ (-x³) and (-9b²a³)² (3³b)²  

+1
(2) Answers
Gracie216

[latex](-9b^2a^3)^2 \cdot (3^3b)^2 = (-9)^2\cdot(b^2)^2 \cdot (a^3)^2 \cdot (3^3)^2\cdot (b)^2 = \\ \\= 81\cdot b^4\cdot a^6 \cdot 3^6\cdot b ^2 = 3^4 \cdot a^6 \cdot b^4\cdot 3^6\cdot b ^2 =\\ \\= 3^{4+6} \cdota^{6} \cdot b ^{4+2} = 3^{10} \cdot a^{6} \cdot b ^6[/latex]

lyssie11234

[latex](-3xy)^3(-x^3)=(-3)^3x^3y^3\cdot(-x^3)=-27x^3y^3\cdot(-x^3)=27x^6y^3\\\\\\(-9b^2a^3)^2\cdot(3^3b^2)^2=(-3^2a^3b^2)^2\cdot(3^3b^2)^2=3^{2\cdot2}a^{3\cdot2}b^{2\cdot2}\cdot3^{3\cdot2}b^{2\cdot2}\\\\=3^4a^6b^4\cdot3^6b^4=3^{4+6}a^6b^{4+4}=3^{10}a^6b^8[/latex]

Add answer